Plasma proteome reflects tissue damage and clinical manifestations in patients with inflammatory myopathies - Yue‐Bei Luo; Josefin Kenrick; Angeles S Galindo‐Feria; Antonella Notarnicola; Ana Daniela Ulloa Navas; Irene Peralta‐Garcia; Orane Demuynck; Andrea Kemp; Valérie Leclair; Karin Lodin; Eveline Van Gompel; Lara Dani; et al. (Arthritis & Rheumatology, 2026)
Objective Tissue‐specific biomarkers that are reliable and associated with clinical manifestations of idiopathic inflammatory myopathy (IIM) are lacking. The blood circulation in individuals serves as a central conduit, allowing communication between tissues and facilitating clearance and recycling of tissue‐derived proteins. Thus, we applied a dual antibody‐based proximity extension assay to profile >1000 proteins in subtypes of patients with IIM. Methods Plasma samples from 201 patients diagnosed with IIM at Karolinska University Hospital were analyzed using Olink Proximity Extension Assay technology. Clinical manifestations, disease activity measurements, and laboratory results were collected. First, we evaluated differential protein abundance across IIM subtypes. Then we calculated tissue scores for each disease subtype using tissue gene expression databases. Finally, interferon (IFN) pathway scores were calculated. Results Plasma from patients with dermatomyositis was enriched for IFN signalling and skin associated proteins, anti‐synthetase syndrome (ASyS) for lung associated proteins, immune‐mediated necrotizing myopathy (IMNM) for muscle associated proteins, and inclusion body myositis for T cell response proteins. Patients with IMNM showed the highest tissue score for skeletal muscles, and ASyS for lung tissue score. Skeletal muscle scores correlated strongly with muscle disease activity visual analog scale scores, creatine kinase levels, and muscle weakness score. Patients with interstitial lung disease along with anti‐MDA5 and those with anti‐Jo1 autoantibodies showed differential enrichment of surfactant proteins and IFN pathway activation. Conclusions Circulatory proteome is a promising tool to capture distinct tissue‐specific responses that correlate with disease activity and tissue injury in patients with IIM. image